-10x+19+6x=59-5x

Simple and best practice solution for -10x+19+6x=59-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10x+19+6x=59-5x equation:


Simplifying
-10x + 19 + 6x = 59 + -5x

Reorder the terms:
19 + -10x + 6x = 59 + -5x

Combine like terms: -10x + 6x = -4x
19 + -4x = 59 + -5x

Solving
19 + -4x = 59 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
19 + -4x + 5x = 59 + -5x + 5x

Combine like terms: -4x + 5x = 1x
19 + 1x = 59 + -5x + 5x

Combine like terms: -5x + 5x = 0
19 + 1x = 59 + 0
19 + 1x = 59

Add '-19' to each side of the equation.
19 + -19 + 1x = 59 + -19

Combine like terms: 19 + -19 = 0
0 + 1x = 59 + -19
1x = 59 + -19

Combine like terms: 59 + -19 = 40
1x = 40

Divide each side by '1'.
x = 40

Simplifying
x = 40

See similar equations:

| 8x^2-9=6x | | 1.2(2t-3)=2.3(t-1) | | a+10=21 | | 3x^2-5b+2=0 | | 14=6x | | 0.2(60)+0.05x=0.01(60+x) | | 5a+2a+3a-3= | | y+(3y+3)=-9 | | 5z-2=17 | | 1+10x=5(2x+2) | | 4x-1-6x+7=11x+3-10x | | 9-8+3=s | | 194-3x10=0 | | s+13=2(s+3) | | 6.9+1.2n=3.54 | | -2=x(x)-9x+23 | | 8-(3+b)=(b-9) | | 4x-1-6x= | | 132x+12=9x-7 | | 72+4+4d=36 | | 22-5x=16+x | | 22-5x=16+6 | | -0.4n+0.305=0.295 | | 3(2y+3)=4y-7 | | 6x-5=2x+5 | | 81-256x^4=0 | | 3y+2(6-4y)=-9 | | 2x+46=30 | | 6x+24=6 | | 60/90=x/2 | | 7y+5=9x+2 | | n=f(t) |

Equations solver categories